Raising the bar with analytics - Kiron, David; Boucher Ferguson, Renee; Prentice, Pamela Kirk (MIT, 2014)
A majority of managers see the importance of increasing the use of analytics in decision making, according to a recent survey of 2,037 managers conducted by MIT Sloan Management Review, in partnership with SAS Institute. More than half of this year's survey respondents strongly agree that their organization needs to step up the use of analytics to make better business decisions -- and that percentage rises to 87% if respondents who agree "somewhat" are included. This finding -- that a majority of survey respondents agree strongly about the need to step up analytics use -- holds true across a range of industries. Several forces, the authors argue, are helping spur managers' interest in analytics, including increased market complexity (for example, omnichannel retailing that encompasses both digital and brick-and-mortar channels) and the availability of better analytics tools and data. The authors report that some companies are sharing their data and analytics with business partners in order to meet strategic business objectives. For example, WellPoint, a U.S. health insurer based in Indianapolis, Indiana, is using analytics to help forge a payment model with physicians that rewards providers when they reduce overall health-care costs and enhance quality and health outcomes. Specifically, WellPoint is converting administrative claims and authorization data into useful information about populations of patients and sharing that information with physicians and their care teams. The survey data suggests that companies for which analytics has improved the ability to innovate are more likely to share data with partners and suppliers. Half of this year's survey respondents somewhat or strongly agree that analytics is helping their organization innovate -- and 16% believe that strongly. Those survey respondents who strongly agree that analytics is helping their organization innovate are much more likely to say they collaborate with partners and suppliers through the use of analytics than respondents who don't think that analytics is helping their company innovate. The authors conclude that as companies use analytics to improve their ability to innovate, they also tend to collaborate more through their use of analytics: Analytics becomes an important medium through which organizations interact with both internal and external stakeholders. Thus, organizations that innovate thanks to analytics don't merely increase their use of analytics in decision ma...
Includes bibliographical references. - Description based on online resource; title from cover page (Safari, viewed April 22, 2015)
Keywords: Quantitative research; Industrial management; Recherche quantitative; Gestion d'entreprise